65-PUB: Relationship between Dietary and Metabolic Control in Patients with DM in Guangdong Province - CHEN, XUANRONG; JIANG, WEI; XIONG, FEI; YANG, LI; XU, WEN; ZENG, LONGYI; CHINA NATIONAL DIABETIC CHRONIC COMPLICATIONSSTUDY GROUP, THE (Diabetes (New York, N.Y.), 2024)
Objective: This subanalysis of a cross-sectional, nationwide study was conducted to assess the dietary status and the relationship between dietary and metabolic control in patients with DM in Guangdong Province. Methods: Data of 1623 residents with DM (48.2% male, average HbA1c: 7.6%, average calorie intake: 1869 kcal/day) in Guangdong aged 18-74 years were included. Participants were asked to finish the questionnaires including the information of consumption of different food components. Blood glucose, HbA1c, lipids, and uric acid were also measured. Results: Among all subjects, 55.5% had hypertension, 92.7% had dyslipidemia. And 46.6% of the subjects were with HbA1c<7%, 35.7% with blood pressure<130/80mmHg, and 7.1% met blood lipid control target. Only 1.7% of the subjects met all three above metabolic targets. The consumption of vegetables and livestock meat in urban areas was lower significantly, while the other food components were higher significantly in urban areas than those in rural areas. As shown in Table 1, the consumptions of food components were significantly different between subjects with optimal glycemic control, achieving LDL-C target, or with normal uric acid levels and those with poor metabolic control. Conclusion: The metabolic control in patients with DM in Guangdong Province was still unsatisfactory. The consumption of different food components may affect the metabolic status.